Modeling and Monte Carlo simulation of call completion success probabilities under the input-output scheme - Nieto Chaupis, Huber (2016)
We present a model of Probability of Success Call Completion (PSCC) from a typical I/O procedure and computationally tested through Monte Carlo simulation with Gaussian profiles. Under the I/O view the input and transfer functions are prepared without to abandon the randomness nature of the phenomenology. Because kernels are required by the I/O formulation, we have assumed that the Dirac-Delta functions play the role of kernels in according to the I/O representation. The results would indicate that under certain circumstances the formulation I/O is valid by a 10% of error respect to the Meo-Ajmone model. However, the weakness of the I/O approach would be in the extraction of a large number of free parameters, which do not necessarily encompasses the dynamic of phenomenon.